Educational Attainment Moderates the Association Between Hippocampal Volumes and Memory Performances in Healthy Older Adults - O’Shea, Deirdre M.; Langer, Kailey; Woods, Adam J.; Porges, Eric C.; Williamson, John B.; O’Shea, Andrew; Cohen, Ronald A. (Frontiers in Aging Neuroscience, 2018)
Objective: To examine whether educational attainment, as a proxy of cognitive reserve, moderated the association between hippocampal volume and episodic verbal memory performance in healthy older adults. Methods: Data from 76 community dwelling older adults were included in the present study. Measures of hippocampal volumes (total, left and right) were obtained using FreeSurfer software. Immediate and delayed verbal recall scores were derived from performances on the California Verbal Learning Test and the Wechsler Memory Scale- Third Edition. Educational attainment was defined by years of education. Linear regression analyses were performed using immediate and delayed recall as dependent variables and hippocampal volumes, years of education, and their interaction terms as independent variables. All analyses were controlled for age, sex, depression, and health status. Results: Hippocampal volume had a positive main effect on episodic memory in all of the models. Additionally, the interaction between hippocampal volume and education was a significant predictor for delayed recall performance but not for immediate recall performance. The positive association between hippocampal volume and delayed recall was greatest in those with more years of education. Conclusions: Larger hippocampal volumes were associated with better immediate and delayed verbal recall and the effect on delayed recall was greatest in those with more years of education. Having higher levels of education, or cognitive reserve, may enable individuals to capitalize on greater structural integrity in the hippocampus to support delayed recall in old age.